DNA Extraction from Bronchial Aspirates for Molecular Cytology: Which Method to Take? - Hans Jürgen Grote; Viola Schmiemann; Mario Sarbia; Alfred Böcking (Analytical Cellular Pathology)
Objective: To date, there are only few systematic reports on the quality of DNA extracted from routine diagnostic cytologic specimens. It was the aim of the present study to evaluate the ability of 50% ethanol/2% carbowax (Saccomanno fixative) to preserve bronchial secretions with high quality genomic DNA as well as to compare different DNA extraction methods. Methods: DNA was extracted from 45 bronchial aspirates by four different extraction protocols. Beside DNA yield, DNA quality with regard to purity, integrity, and PCR success rate were investigated. Results: No fragmentation of sample DNA due to the fixative was detected. It was preserved as high molecular weight DNA. DNA yield, purity, and integrity were dependent on the DNA extraction method to some extend. Irrespective of the DNA extraction method the PCR success rate for amplification of β‐globin gene fragments (268, 536, and 989 bp) was 100%. Conclusions: A fixative containing 50% ethanol/2% carbowax preserves high quality DNA which is well suited for PCR‐based assays regardless of the extraction protocol used. The selection of the DNA extraction protocol has to be adjusted to the circumstances of application.